2022
DOI: 10.1097/jnr.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Motor Function Rehabilitation Program for Acute Ischemic Stroke: A Randomized Pilot Study

Abstract: Background Rehabilitation care for patients with stroke in the acute stage must be strengthened. However, the evidence on how to strengthen this care is insufficient. Purpose This article was designed to evaluate the feasibility and effectiveness of implementing a nurse-led motor function rehabilitation program on patients with acute ischemic stroke. Methods From January to October 2018, patients with initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Such teams are directed by physicians trained in physical medicine and rehabilitation (physiatrists) or by neurologists who have specialized training or board certification in rehabilitation medicine. Other health professionals who play an essential role in the process include social workers, psychologists, psychiatrists, and counselors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Such teams are directed by physicians trained in physical medicine and rehabilitation (physiatrists) or by neurologists who have specialized training or board certification in rehabilitation medicine. Other health professionals who play an essential role in the process include social workers, psychologists, psychiatrists, and counselors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The second implication is that a combination of additional training is effective in improving patients’ ADL. Previous studies on the content of additional training have reported the effectiveness of therapist-led self-exercise ( 15 ) and the introduction of a nurse-led exercise intervention programme ( 17 , 18 ). However, it was unclear which type of exercise was more effective and the combined effects of these additional training approaches remained ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search initially found 821 studies: 467 studies were omitted as duplicates, leaving 354 studies that were screened for relevancy. We finally included a total of 16 studies (Langhorne et al, 2010;Kim, 2012;Yue et al, 2013;McAlister et al, 2014;Wong and Yeung, 2015;Zhou et al, 2019;Ademuyiwa and Okubadejo, 2021;Li et al, 2021;Wang et al, 2021Wang et al, , 2022aAi et al, 2022;Cha et al, 2022;Deng et al, 2022;Urcan and Kolcu, 2022;Zheng et al, 2023). Out of them 12 were chosen for SR and MA (Langhorne et al, 2010;Yue et al, 2013;McAlister et al, 2014;Wong and Yeung, 2015;Zhou et al, 2019;Li et al, 2021;Wang et al, 2021Wang et al, , 2022aAi et al, 2022;Cha et al, 2022;Deng et al, 2022;Zheng et al, 2023), contrary to four studies that were only eligible for SR (Kim, 2012;Ademuyiwa and Okubadejo, 2021;Urcan and Kolcu, 2022;Wang et al, 2022b).…”
Section: Literature Searchmentioning
confidence: 99%
“…Our study finally included a total of 16 studies with overall 2072 enrolled patients; the studies were primarily clinical trials (Langhorne et al, 2010;Kim, 2012;Yue et al, 2013;McAlister et al, 2014;Wong and Yeung, 2015;Zhou et al, 2019;Li et al, 2021;Wang et al, 2021Wang et al, , 2022aAi et al, 2022;Cha et al, 2022;Urcan and Kolcu, 2022) in addition to only one cohort study (Deng et al, 2022) and two quasiexperimental studies (Ademuyiwa and Okubadejo, 2021;Zheng et al, 2023). The included studies were conducted in China, Canada, Australia, Sweden, Nigeria, the UK, and South Korea.…”
Section: Baseline Characteristics Of the Included Populationmentioning
confidence: 99%
See 1 more Smart Citation